Thermoplastic elastomer as well as preparation method and application thereof

The thermoplastic elastomer prepared through multi-component composite uses the synergistic effect of styrene-based copolymers, polyolefin resins, polyacrylic hydrophilic resins, paraffin oils and compatibility agents to solve the performance problems of sealing materials in high temperature and water environments, achieve high rebound performance and waterproofing effects, and meet the temperature resistance and waterproofing needs in many fields.

CN119798899AActive Publication Date: 2025-04-11KINGFA SCI & TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510053678.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The rebound performance of existing sealing materials in high temperature environments has deteriorated, resulting in poor sealing effect and liquid leakage is prone to occur when contacting water, making it difficult to meet the needs of high temperature resistance and waterproofing.

Method used

Through multi-component combination, a thermoplastic elastomer is prepared, including styrene copolymers, polyolefin resins, polyacrylic hydrophilic resins, paraffin oils and compatibilizers. The synergistic effect of these components is used to make the material expand when it encounters water, and restore its original size after loss of water, maintaining excellent high-temperature rebound performance.

Benefits of technology

It achieves high rebound performance and waterproof performance of materials in high temperature environments, improves sealing effect, and meets the temperature resistance and waterproof needs of municipal waterproofing, automobiles, construction, home appliances and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240730060000121
    Figure BDA0005240730060000121
  • Figure BDA0005240730060000131
    Figure BDA0005240730060000131
  • Figure BDA0005240730060000132
    Figure BDA0005240730060000132
Patent Text Reader

Abstract

The invention relates to a thermoplastic elastomer as well as a preparation method and application thereof, and the thermoplastic elastomer comprises the following components in parts by weight: 5-50 parts of a styryl copolymer, 1-30 parts of polyolefin resin, 20-80 parts of polyacrylic acid hydrophilic resin, 10-60 parts of paraffin oil and 1-20 parts of a compatilizer. Through compounding of multiple components, the thermoplastic elastomer material which has excellent strength and high-temperature resilience and can expand when encountering water and restore the original size after water loss is obtained, the sealing effect of the material is improved, and the thermoplastic elastomer material is suitable for the fields with waterproof requirements such as municipal waterproofing, automobiles, buildings and household appliances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a thermoplastic elastomer and a preparation method and application thereof. Background Art

[0002] Styrene copolymers are the cheapest thermoplastic elastomers and are the most widely used. They are block copolymers made of hard polystyrene segments interconnected with flexible segments such as polybutadiene, polyisoprene, ethylene propylene rubber or styrene. These materials have good mechanical properties, thermal stability, soft touch, low odor and emission, safety and non-toxicity, and are widely used in the fields of automobiles, construction, toys, medical treatment, daily consumer goods, home appliances, etc.

[0003] In automobiles, buildings, home appliances and other applications, there are many product applications that use rubber seals, such as automobile window seals, glass skylight seals, washing machine seals, etc. For example, CN109456544A discloses a method for preparing environmentally friendly valve seals, including the following steps: mixing polystyrene, EPDM rubber, titanate coupling agent, and antioxidant to obtain a rubber compound; mixing expanded graphite, vermiculite powder, nano-mica powder, polyacrylonitrile-based carbon fiber, calcium sulfate whisker, aluminum borate whisker, carrageenan, sodium carboxymethyl cellulose, and water, ultrasonically dispersing, and spray drying to obtain a dispersed material; feeding the rubber compound, the dispersed material, and microcrystalline wax into a twin-screw extruder for extrusion, and granulating to obtain an environmentally friendly valve seal, wherein the obtained seal is halogen-free and flame-retardant, resistant to heat air aging, high in tensile strength, and high in elongation at break.

[0004] CN108707276A discloses a method for preparing a flame-retardant sound-insulating sealing strip for a vehicle, which comprises the following steps: placing nickel ferrite fiber, a chain extender and a foaming agent in a polymer emulsion for heating reaction to obtain a modified nickel ferrite fiber, ultrasonically washing and drying the composite fiber, and then subjecting the composite fiber to a high-temperature treatment at 200-250°C for 10-20 minutes to obtain the composite fiber; placing EVA resin, phenolic resin, composite fiber, mesoporous silica, acrylonitrile-butadiene-styrene copolymer, α-methylstyrene-acrylonitrile copolymer and an antioxidant into a twin-screw extruder, over-melting and extruding, granulating, and obtaining a composite masterbatch; performing secondary mold opening and injection molding on the composite masterbatch to obtain a flame-retardant sound-insulating sealing strip for a vehicle, wherein the obtained vehicle sealing strip has light weight, good sound absorption effect and good flame retardancy, and meets the requirements of modern lightweight, environmental protection and comfort.

[0005] However, these sealing products often have problems with poor high temperature resistance and water resistance. In a long-term high temperature environment, the rebound performance will decrease, resulting in poor sealing effect. Liquid leakage is prone to occur in rainy days or in water contact application scenarios. Therefore, how to provide a sealing material that is resistant to high temperatures and not easy to leak has become a problem that needs to be solved urgently. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a thermoplastic elastomer and a preparation method and application thereof. Through multi-component compounding, the thermoplastic elastomer expands when exposed to water and recovers when water is lost. At the same time, it has excellent high-temperature rebound performance, improves the sealing effect of the material, and can meet the temperature and waterproof requirements of rubber sealing parts such as municipal waterproofing, automobiles, construction, and home appliances.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a thermoplastic elastomer, which comprises the following components, in parts by weight: 5-50 parts of a styrene-based copolymer, 1-30 parts of a polyolefin resin, 20-80 parts of a polyacrylic hydrophilic resin, 10-60 parts of paraffin oil, and 1-20 parts of a compatibilizer.

[0009] The present invention adopts a styrene-based copolymer and a polyolefin resin to compound, so that the obtained thermoplastic elastomer has excellent mechanical strength and high-temperature resilience performance; further combined with a polyacrylic acid hydrophilic resin, the water absorption and water loss capacity of the thermoplastic elastomer is regulated, so that the volume expands after absorbing water and recovers to the original size after losing water, thereby avoiding liquid leakage of the sealing material under high temperature conditions or after contact with water; in addition, the addition of a compatibilizer and paraffin oil improves the compatibility of the system, and a thermoplastic elastomer with significantly improved sealing performance is obtained, which meets the application needs of more fields.

[0010] The styrene-based copolymer is present in an amount of 5-50 parts, for example, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or 45 parts.

[0011] The polyolefin resin is 1-30 parts, for example, 2 parts, 5 parts, 8 parts, 10 parts, 15 parts, 20 parts or 25 parts.

[0012] The polyacrylic acid hydrophilic resin is 20-80 parts, for example, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 60 parts or 70 parts.

[0013] The paraffin oil is 10-60 parts, for example, can be 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or 55 parts.

[0014] The compatibilizer is 1-20 parts, for example, 2 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts or 18 parts.

[0015] Preferably, the thermoplastic elastomer comprises the following components, in parts by weight: 10-23 parts of a styrene-based copolymer (for example, 12 parts, 15 parts, 18 parts, 20 parts or 22 parts, etc.), 5-17 parts of a polyolefin resin (for example, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts or 16 parts, etc.), 40-65 parts of a polyacrylic acid hydrophilic resin (for example, 42 parts, 45 parts, 48 ​​parts, 50 parts, 52 parts, 55 parts, 58 parts or 60 parts, etc.), 20-35 parts of paraffin oil (for example, 22 parts, 25 parts, 28 parts, 30 parts or 32 parts, etc.), and 5-13 parts of a compatibilizer (for example, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts or 12 parts, etc.).

[0016] As a preferred technical solution of the present invention, the mass percentage of the styrene-based copolymer in the thermoplastic elastomer is 10-23%, for example, it can be 11%, 13%, 15%, 17%, 19% or 21%.

[0017] As a preferred technical solution of the present invention, the mass percentage of the polyolefin resin in the thermoplastic elastomer is 5-17%, for example, it can be 6%, 8%, 10%, 12%, 14% or 16%.

[0018] As a preferred technical solution of the present invention, the mass percentage of the polyacrylic acid hydrophilic resin in the thermoplastic elastomer is 40-65%, for example, it can be 41%, 43%, 45%, 47%, 49%, 51%, 53%, 55%, 57%, 59%, 61% or 63%, etc., and is further preferably 42-58%.

[0019] As a preferred technical solution of the present invention, the mass percentage of paraffin oil in the thermoplastic elastomer is 15-35%, for example, it can be 18%, 20%, 21%, 23%, 25%, 27%, 29%, 31% or 33%.

[0020] As a preferred technical solution of the present invention, the mass percentage of the compatibilizer in the thermoplastic elastomer is 5-13%, for example, it can be 6%, 7%, 8%, 9%, 10%, 11% or 12%.

[0021] In the present invention, the styrene-based copolymer includes a copolymerization product of styrene and an olefin monomer and / or a hydrogenation product of a copolymer of styrene and an olefin monomer; the olefin monomer illustratively includes but is not limited to: any one of ethylene, propylene, butylene, butadiene, and isoprene, or a combination of at least two thereof.

[0022] It should be noted that the styrene-based copolymer includes a styrene-based random copolymer and / or a styrene-based block copolymer, preferably a styrene-based block copolymer.

[0023] Preferably, the styrene-based copolymer includes any one of styrene-butadiene copolymer (SBS), styrene-ethylene-butylene-styrene copolymer (SEBS) or styrene-poly(ethylene / ethylene / propylene)-styrene copolymer (SEEPS) or a combination of at least two thereof.

[0024] Preferably, the styrene-based copolymer includes a linear styrene-based copolymer and / or a network-structured styrene-based copolymer, and a linear styrene-based copolymer is further preferred. As a preferred technical solution of the present invention, the use of a linear styrene-based copolymer is beneficial to the water absorption and water loss of the thermoplastic elastomer. When other network cross-linked structures (such as a binary star structure) are used, the styrene-based copolymer has a strong wrapping property for the polyolefin resin, resulting in difficulty in water absorption and water loss, and the "elastic waterproof" effect cannot be achieved.

[0025] Preferably, the weight average molecular weight (Mw) of the styrene-based copolymer is 60000-300000 g / mol, for example, 70000 g / mol, 80000 g / mol, 100000 g / mol, 120000 g / mol, 150000 g / mol, 160000 g / mol, 170000 g / mol, 180000 g / mol, 190000 g / mol, 200000 g / mol, 2 The molecular weight of the present invention is preferably 0.05000 g / mol, 210000 g / mol, 215000 g / mol, 220000 g / mol, 225000 g / mol, 230000 g / mol, 240000 g / mol, 250000 g / mol, 260000 g / mol or 280000 g / mol, further preferably 150000-250000 g / mol, more preferably 200000-230000 g / mol.

[0026] As a preferred technical solution of the present invention, a styrene-based copolymer with a specific weight-average molecular weight is compounded with other components to improve the tensile strength of the obtained thermoplastic elastomer and reduce the compression permanent deformation.

[0027] For example, the styrene-based copolymer in the present invention can be selected from commercially available products, such as Gobalprene7551, Taipol 6151, Kraton G1651, and the like.

[0028] Preferably, the polyolefin resin includes polypropylene (PP) and / or polyethylene (PE), more preferably polypropylene.

[0029] Preferably, the polypropylene includes copolymer polypropylene and / or homopolypropylene, and more preferably homopolypropylene.

[0030] Preferably, the polyethylene includes low-density polyethylene and / or high-density polyethylene.

[0031] As the preferred technical method of the present invention, homopolymer polypropylene has better compatibility with other components in the thermoplastic elastomer, which is conducive to forming a uniform and stable system and improving the mechanical strength and high-temperature resilience of the material.

[0032] Preferably, the melt index of the polypropylene at 230° C. and 2.16 kg is 1-10 g / 10 min, for example, 2 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 8 g / 10 min or 9 g / 10 min.

[0033] Preferably, the melt index of the polyethylene at 190°C and 2.16kg is 1-10g / 10min, for example, 2g / 10min, 3g / 10min, 4g / 10min, 5g / 10min, 6g / 10min, 7g / 10min, 8g / 10min or 9g / 10min.

[0034] As a preferred technical solution of the present invention, a polyolefin resin with a specific melt index is compounded with a styrene-based copolymer, a polyacrylic acid hydrophilic resin, paraffin oil and a compatibilizer, which is more conducive to making the thermoplastic elastomer have high strength, excellent high-temperature resilience and water absorption performance. If the melt index of the polyolefin resin is too high, the resilience of the elastomer material will be reduced and the water absorption performance will also be reduced.

[0035] Preferably, the polyacrylic acid-based hydrophilic resin includes polyacrylic acid and / or polyacrylic acid salt.

[0036] Preferably, the polyacrylate includes any one of sodium polyacrylate, potassium polyacrylate, and ammonium polyacrylate, or a combination of at least two thereof, and sodium polyacrylate is more preferred.

[0037] Preferably, the particle size (raw material) of the polyacrylic acid hydrophilic resin is 20-100 mesh, for example, 30 mesh, 40 mesh, 50 mesh, 60 mesh, 70 mesh, 80 mesh or 90 mesh.

[0038] The present invention has no particular limitation on paraffin oil, and commercially available Class II hydrogenated paraffin oil may be used, for example, Formosa Plastics 500N, CNOOC 150N, Hansheng Pionier 2071P, etc.

[0039] Preferably, the kinematic viscosity of the paraffin oil at 40° C. is 60-150 cst, for example, 70 cst, 80 cst, 90 cst, 110 cst, 120 cst, 130 cst or 140 cst.

[0040] Preferably, the compatibilizer includes any one of ethylene-acrylic acid copolymer (EAA), ethylene-vinyl acetate copolymer (EVA), maleic anhydride grafted polyolefin or maleic anhydride grafted ethylene propylene diene rubber (EPDM) or a combination of at least two thereof, more preferably ethylene-acrylic acid copolymer and / or maleic anhydride grafted polyolefin, more preferably ethylene-acrylic acid copolymer.

[0041] As a preferred technical solution of the present invention, using ethylene-acrylic acid copolymer as a compatibilizer can further improve the compatibility of the system, thereby ensuring that the material has excellent tensile strength and water absorption expansion rate.

[0042] Preferably, the melt index of the ethylene-acrylic acid copolymer at 190°C and 2.16kg is 8-15g / 10min, for example, 9g / 10min, 10g / 10min, 11g / 10min, 12g / 10min, 13g / 10min or 14g / 10min.

[0043] Preferably, the mass percentage of the acrylic acid-based structural units in the ethylene-acrylic acid copolymer is 5-20%, for example, it can be 6%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, etc., and more preferably 6.5-15%.

[0044] Preferably, the maleic anhydride grafted polyolefin includes any one of maleic anhydride grafted polypropylene (PP), maleic anhydride grafted ethylene / α-olefin copolymer (POE) or maleic anhydride grafted polyethylene or a combination of at least two thereof.

[0045] Preferably, the maleic anhydride grafted polypropylene has a melt index of 50-200 g / 10 min at 230° C. and 2.16 kg, for example, 60 g / 10 min, 80 g / 10 min, 100 g / 10 min, 120 g / 10 min, 140 g / 10 min, 150 g / 10 min, 160 g / 10 min or 180 g / 10 min, etc.

[0046] Preferably, the maleic anhydride grafted polyethylene comprises maleic anhydride grafted linear low density polyethylene (LLDPE).

[0047] Preferably, the maleic anhydride grafted polyethylene has a melt index of 0.5-10 g / 10 min at 190° C. and 2.16 kg, for example, 1 g / 10 min, 2 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 8 g / 10 min or 9 g / 10 min, etc.

[0048] It should be noted that the thermoplastic elastomer of the present invention may also include any other additives that are added with motivation in the art.

[0049] Preferably, the thermoplastic elastomer further comprises 0.2-0.8 parts by weight of an antioxidant, for example, 0.25 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight or 0.7 parts by weight.

[0050] Preferably, the antioxidant includes any one of hindered phenol antioxidants, hindered amine antioxidants, phosphite antioxidants, and thioester antioxidants, or a combination of at least two of them.

[0051] Preferably, the antioxidant includes any one or a combination of at least two of 2,6-di-tert-butyl-4-methylphenol, pentaerythritol tetrakis (3,5-di-tert-butyl-4-hydroxyhydrocinnamate) (antioxidant 1010), 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1076), 1,3,5-tris (4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) -1,3,5-triazine-2,4,6-(1H,3H,5H)-trione (antioxidant 1790), tris (2,4-di-tert-butyl) phenyl phosphite (antioxidant 168) or pentaerythritol tetrakis (3-laurylthiopropionate) (antioxidant 412S).

[0052] In a second aspect, the present invention provides a method for preparing the thermoplastic elastomer as described in the first aspect, the preparation method comprising the following steps:

[0053] The thermoplastic elastomer is obtained by mixing a styrene-based copolymer, a polyolefin resin, a polyacrylic acid hydrophilic resin, paraffin oil, a compatibilizer and an optional antioxidant, extruding and granulating.

[0054] Preferably, the mixing is carried out in a high-speed mixer.

[0055] Preferably, the extrusion is carried out in a twin-screw extruder.

[0056] Preferably, the aspect ratio of the twin-screw extruder is ≥52, for example, it may be 53, 55, 60, 65, 70, 75 or 80, etc.

[0057] Preferably, the rotation speed of the twin-screw extruder is 180-450 rpm, for example, 200 rpm, 220 rpm, 250 rpm, 300 rpm, 350 rpm or 400 rpm.

[0058] Preferably, the temperature of the twin-screw extruder is 140-180°C, for example, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, etc.

[0059] Preferably, the extrusion feed rate is 150-450 kg / h, for example, 180 kg / h, 200 kg / h, 250 kg / h, 300 kg / h, 350 kg / h or 400 kg / h.

[0060] Preferably, the granulation is carried out in a granulator.

[0061] Preferably, the extrusion and granulation operations include plasticizing through a twin-screw extruder, feeding into a cold water tank, and then pulling into a pelletizer for pelletizing to obtain the thermoplastic elastomer.

[0062] In a third aspect, the present invention provides a sealing component, wherein the raw material for preparing the sealing component includes the thermoplastic elastomer as described in the first aspect.

[0063] The sealing element provided by the present invention can be used as a rubber sealing part in applications requiring waterproofing, such as municipal waterproofing, automobiles, buildings, and household appliances, to achieve excellent waterproof and temperature-resistant effects.

[0064] Compared with the prior art, the present invention has at least the following beneficial effects:

[0065] The thermoplastic elastomer provided by the present invention includes a styrene-based copolymer, a polyolefin resin, a polyacrylic hydrophilic resin, paraffin oil and a compatibilizer. The components work together to achieve "elastic water absorption", thereby improving the temperature resistance and waterproof performance of the material while maintaining excellent mechanical strength, thereby expanding the application field of the obtained thermoplastic elastomer as a sealing material. DETAILED DESCRIPTION

[0066] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0067] In the following specific implementation of the present invention, the materials involved are as follows:

[0068] (1) Styrene-based copolymers

[0069] SEBS1, SEBS 7550U, Li Changrong, linear structure;

[0070] SEBS2, SEBS 7551, Li Changrong, linear structure;

[0071] SEBS3, SEBS YH-688, Yuehua, two-star structure;

[0072] SBS, SBS 3566, Huizhou Li Changrong, linear structure.

[0073] (2) Polyolefin resin

[0074] PP1, homopolymer polypropylene, PPH-T03, Sinopec, melt index at 230°C, 2.16kg is 3.0g / 10min;

[0075] PP2, copolymer polypropylene, Globalene ST611M, Li Changrong, melt index of 1.8 g / 10 min at 230 °C and 2.16 kg;

[0076] PP3, homopolymer polypropylene, Daqing Refining and Chemical, melt index at 230℃ and 2.16kg is 5.4g / 10min;

[0077] PP4, homopolymer polypropylene, Zhenhai Refining and Chemical, melt index at 230℃ and 2.16kg is 26g / 10min;

[0078] Linear low-density polyethylene (LLDPE), DFDA-7042, Guangzhou Petrochemical, melt index at 190°C, 2.16kg is 2.0g / 10min.

[0079] (3) Hydrophilic resin

[0080] Sodium polyacrylate, GS-3100H, LG Chem;

[0081] Polyacrylamide, 18 million anionic PAM, Zibo Lanerqing.

[0082] (4) Paraffin oil

[0083] Paraffin oil, 500N, Formosa Plastics, kinematic viscosity at 40°C 90cst.

[0084] (5) Compatibilizer

[0085] EAA, EAA Nucrel 3990, Dow Chemical;

[0086] Maleic anhydride grafted polypropylene (MAH-PP), FH118, Ganzhou Nengzhiguang;

[0087] Maleic anhydride grafted linear low-density polyethylene (MAH-LLDPE), PC-31-4, Foshan Bochen.

[0088] (6) Antioxidants

[0089] Antioxidant 1010, Irganox 1010, BASF.

[0090] (7) EPDM

[0091] EPDM 3072EPM, Sinopec Mitsui, Mooney viscosity at 125℃ is 51MU.

[0092] Example 1

[0093] A thermoplastic elastomer, which comprises, by weight, 15 parts of SEBS (SEBS 7550U), 8 parts of homopolypropylene (Z30-S), 50 parts of sodium polyacrylate (GS-3100H), 20 parts of paraffin oil (500N), 7 parts of compatibilizer EAA, and 0.2 parts of antioxidant 1010 (Irganox 1010);

[0094] The thermoplastic elastomer is prepared by the following method:

[0095] The components were mixed evenly in a high-speed mixer, and added into a twin-screw extruder with a length-to-diameter ratio of 52 at 300 kg / h. The speed of the twin-screw extruder was 300 rpm and the temperature was 170°C. After plasticization by the twin-screw extruder, it was fed into a cold water tank and then pulled into a pelletizer for pelletizing to obtain the thermoplastic elastomer.

[0096] The thermoplastic elastomer provided in Example 1 was subjected to the following performance tests:

[0097] (1) Shore hardness

[0098] Thermoplastic elastomer was added into the injection molding machine and injection molded into a square plate with a length, width and height of 100mm×100mm×2mm at 190°C. After standing for 24 hours at 23°C and a relative humidity of 50%, three square plates were stacked into a sample with a thickness of 6mm. The hardness of the sample was measured and recorded using a Shore A hardness tester.

[0099] (2) Tensile strength

[0100] The thermoplastic elastomer was added into an injection molding machine and injection molded at 190°C into a square plate with a length, width and height of 100 mm × 100 mm × 2 mm. It was cut into Type 1A specimens in the ISO 37-2024 standard with a cutter and tested with a universal tensile testing machine in accordance with the ISO 37-2024 standard at a tensile rate of 500 mm / min.

[0101] (3) Water absorption expansion rate

[0102] Add the thermoplastic elastomer into the injection molding machine and process it into a sample with a size of 100mm×10mm×2mm at 190℃. Use a vernier card to measure and record the volume of the sample before immersion. Then completely immerse the sample in 5 liters of distilled water at 23℃, take it out after standing for 24 hours, and immediately measure the size of the sample to obtain the volume of the sample after immersion. The water absorption expansion rate is calculated by the following formula:

[0103] Water absorption expansion ratio = 100% × (volume of sample after immersion - volume of sample before immersion) / volume of sample before immersion.

[0104] (4) Water loss volume change rate

[0105] Add the thermoplastic elastomer into the injection molding machine and process it into a sample with a size of 100mm×10mm×2mm at 190℃, and record the weight of the sample. Soak the above sample in distilled water according to the water absorption expansion rate measurement method, place it in a 100℃ oven for 24 hours, and measure the weight of the sample. When the weight difference before and after soaking is less than 0.1g, the size of the sample after water loss is tested to obtain the volume of the sample after drying. The water loss volume change rate is calculated by the following formula:

[0106] Water loss volume change rate = 100% × (volume of sample after drying - volume of sample before immersion) / volume of sample before immersion.

[0107] (5) Permanent compression set

[0108] Thermoplastic elastomer was added to the injection molding machine, and a round block conforming to the GB / T 7759.1-2015A type specimen size was obtained at 190°C, with a size of 29±0.5mm and a height of 12.5±0.5mm. According to GB / T7759.1-2015A type, method A, the permanent compression deformation was tested at 70°C for 22 hours. The smaller the value, the better the high temperature resilience of the material.

[0109] The test results are summarized in Table 1.

[0110] Examples 2-13, Comparative Examples 1-5

[0111] A thermoplastic elastomer, which differs from Example 1 in that the formula of the thermoplastic elastomer is different, as shown in Table 1 and Table 2; wherein the dosage unit of each component is "parts by weight" of the solid content; the preparation method and performance testing method of the thermoplastic elastomer are the same as those of Example 1.

[0112] Table 1

[0113]

[0114]

[0115] Table 2

[0116]

[0117]

[0118] It can be seen from the test results that the present invention obtains a thermoplastic elastomer material that expands when exposed to water and restores when dehydrated by compounding a styrene-based copolymer, a polyolefin resin, a polyacrylic acid hydrophilic resin, paraffin oil and a compatibilizer, and the Shore hardness is 44-62A, the volume expansion rate after water absorption is ≥248%, the volume change rate after water loss is ≤15%, the tensile strength is ≥1.2MPa, and the permanent compression deformation at 70°C / 22 hours is ≤82%; in a further preferred technical scheme, the volume expansion rate of the thermoplastic elastomer material after water absorption is 301-372%, the volume change rate after water loss is ≤8%, the tensile strength is ≥2.8MPa, and the permanent compression deformation at 70°C / 22 hours is ≤68%, which meets the application requirements of heat resistance, waterproofness and high strength of the sealing material.

[0119] By comparing Example 2 with Example 3, it can be seen that the present invention can obtain the best water absorption expansion rate and volume change rate after water loss by selecting SEBS with a linear structure, while the star-shaped SEBS network structure easily produces a wrapping effect on the resin matrix, resulting in the hydrophilic resin being unable to expand freely and the volume expansion rate after water absorption being reduced.

[0120] By comparing Example 2 with Examples 4 and 8, it can be seen that the present invention uses EAA as a compatibilizer, which has better compatibility with the matrix resin and improves the permanent compression set, water absorption expansion rate and tensile strength of the obtained thermoplastic elastomer.

[0121] By comparing Example 2 with Examples 6 and 7, it can be seen that under the condition of adding a specific proportion of hydrophilic resin, the volume expansion rate after water absorption reaches the best, and the volume expansion rate does not increase after continuing to increase the hydrophilic resin, while the volume expansion rate after water absorption decreases when the proportion of hydrophilic resin is reduced.

[0122] By comparing Example 2 with Examples 9 and 10, it can be seen that the preferred polypropylene homopolymer is the polyolefin resin component of the present invention, which is superior to the copolymer polypropylene and the linear low-density polyethylene in terms of permanent compression deformation, mainly because the melting temperature (T m ) is higher than copolymer polypropylene and linear low-density polyethylene, which makes the blend resin have low molecular activity at high temperature, resulting in smaller permanent deformation.

[0123] Furthermore, it can be seen from Examples 2, 11 and 12 that the preferred melt index of the polypropylene of the present invention is 1-10 g / 10 min, and when compounded with other components, it can obtain better resilience and water absorption performance; if the melt index of the polypropylene is too high, it will lead to an increase in the compression permanent set of the material, a decrease in the water absorption rate, and an increase in the volume change rate after water loss.

[0124] It can be seen from Examples 2 and 13 that, in the present invention, the thermoplastic elastomer using SEBS has better performance in terms of strength, water absorption and high-temperature resilience than SBS.

[0125] By comparing Example 2 with Comparative Example 1, it can be seen that the thermoplastic elastomer of the present invention uses sodium polyacrylate as the hydrophilic resin. At the same addition ratio, the volume expansion rate after water absorption is significantly better than that of polyacrylamide. This is mainly because the ionic bonds in the structure of sodium polyacrylate are easier to exchange ions with water than the amino covalent bonds in polyacrylamide, thereby having stronger water absorption. At the same time, the compounding of sodium polyacrylate with other components also helps to improve the high-temperature resilience and strength of the thermoplastic elastomer.

[0126] By comparing Example 2 with Comparative Examples 2-5, it can be seen that the present invention improves the tensile strength of the material and obtains a lower permanent compression deformation by compounding styrene-based copolymers, polyolefin resins with polyacrylic acid hydrophilic resins, paraffin oil, and compatibilizers, thereby increasing the water absorption volume expansion rate of the material, so that the resulting thermoplastic elastomer has the "elastic water absorption" effect of expanding when exposed to water and recovering to its original size when dehydrated.

[0127] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A thermoplastic elastomer, characterized in that: The thermoplastic elastomer comprises the following components in parts by weight: 5-50 parts of styrene-based copolymer, 1-30 parts of polyolefin resin, 20-80 parts of polyacrylic acid hydrophilic resin, 10-60 parts of paraffin oil, and 1-20 parts of compatibilizer.

2. The thermoplastic elastomer according to claim 1, characterized in that The thermoplastic elastomer comprises the following components in parts by weight: 10-23 parts of styrene-based copolymer, 5-17 parts of polyacrylic polyolefin resin, 40-65 parts of hydrophilic resin, 20-35 parts of paraffin oil, and 5-13 parts of compatibilizer.

3. The thermoplastic elastomer according to claim 1, characterized in that The styrene-based copolymer includes any one or a combination of at least two of a styrene-butadiene copolymer, a styrene-ethylene-butylene-styrene copolymer, or a styrene-poly(ethylene / ethylene / propylene)-styrene copolymer; Preferably, the styrene-based copolymer comprises a linear structure styrene-based copolymer; Preferably, the weight average molecular weight of the styrene-based copolymer is 60,000-300,000 g / mol, more preferably 150,000-250,000 g / mol.

4. The thermoplastic elastomer according to claim 1, characterized in that The polyolefin resin includes polypropylene and / or polyethylene, preferably polypropylene; Preferably, the polypropylene includes copolymer polypropylene and / or homopolypropylene, and more preferably homopolypropylene; Preferably, the polyethylene comprises low-density polyethylene and / or high-density polyethylene; Preferably, the melt index of the polypropylene at 230° C. and 2.16 kg is 1-10 g / 10 min; and / or the melt index of the polyethylene at 190° C. and 2.16 kg is 1-10 g / 10 min.

5. The thermoplastic elastomer according to claim 1, characterized in that The polyacrylic acid hydrophilic resin includes polyacrylic acid and / or polyacrylic acid salt; Preferably, the mass percentage of the polyacrylic acid hydrophilic resin in the thermoplastic elastomer is 40-65%.

6. The thermoplastic elastomer according to claim 1, characterized in that The compatibilizer includes any one or a combination of at least two of ethylene-acrylic acid copolymer, ethylene-vinyl acetate copolymer, maleic anhydride grafted polyolefin or maleic anhydride grafted ethylene propylene diene rubber, preferably ethylene-acrylic acid copolymer; Preferably, the maleic anhydride grafted polyolefin includes any one of maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene / α-olefin copolymer or maleic anhydride grafted polyethylene or a combination of at least two thereof.

7. The thermoplastic elastomer according to claim 1, characterized in that The thermoplastic elastomer also includes 0.2-0.8 parts by weight of an antioxidant; Preferably, the antioxidant includes any one or a combination of at least two of 2,6-di-tert-butyl-4-methylphenol, pentaerythritol tetrakis (3,5-di-tert-butyl-4-hydroxyhydrocinnamate), 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5-tris (4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) -1,3,5-triazine-2,4,6- (1H,3H,5H) -trione, tris (2,4-di-tert-butyl) phenyl phosphite or pentaerythritol tetrakis (3-laurylthiopropionate).

8. A method for preparing a thermoplastic elastomer according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The thermoplastic elastomer is obtained by mixing a styrene-based copolymer, a polyolefin resin, a polyacrylic acid hydrophilic resin, paraffin oil, a compatibilizer and an optional antioxidant, extruding and granulating.

9. The preparation method according to claim 8, characterized in that: The mixing is carried out in a high-speed mixer; Preferably, the extrusion is carried out in a twin-screw extruder; Preferably, the aspect ratio of the twin-screw extruder is ≥52; Preferably, the rotation speed of the twin-screw extruder is 180-450 rpm; Preferably, the temperature of the twin-screw extruder is 140-180°C; Preferably, the feed rate of the extrusion is 150-450 kg / h; Preferably, the granulation is carried out in a granulator.

10. A sealing member, characterized in that: The raw material for preparing the sealing element includes the thermoplastic elastomer as described in any one of claims 1-7.

Citation Information

Patent Citations

  • Preparation method of automotive flame-retardant sound-proof seal strip

    CN108707276A

  • Preparation method of environment-friendly valve sealing part

    CN109456544A

  • Thermoplastic water-swellable elastomer and preparing method and application thereof

    CN104693665A

  • Thermoplastic elastomer refrigerator door sealing strip material and preparation method

    CN108795064A

  • Water-absorbing and swelling resin composition

    JP1989126373A